Morphometric Study of Lumbar Spine in Nepalese Adult Population attending a Diagnostic Center - Shahi, Rajive Raj; Regmi, Dosti; Budathoki, Lee; Pant, Sujata; Pokharel, Anish; Sapkota, Mani Raj (Journal of Karnali Academy of Health Sciences, 2021)
Background: Magnetic Resonance Imaging (MRI) is the modality of choice for the evaluation of the lumbar spine for the cause of backache and radiculopathy. The central spinal canal and neural foramen stenosis cause nerve root entrapment and radiculopathy and most of the spinal surgeries in adult patients are related to spinal stenosis. The development of a nomogram of the various morphological parameters of the central spinal canal, lateral recess, and neural foramina in the lumbar spine MRI is essential to determine the degree of acquired stenosis as well as a plan of intervention and instrumentation in surgeries. Methods: A retrospective descriptive study of the lumbar spine MRI of 107 Nepalese population (59 male and 48 female) between 18 to 50 years with no central spinal canal or neural foramen narrowing and no history of congenital anomaly, trauma, or surgery were done for six months between 01 September 2020, and 28 February 2021. Thecal sac diameters, lateral recess depth/angle, and neural foramen dimensions were measured and tabulated. Calculation of the mean and standard deviation was done in Statistical Package for Social Sciences (SPSS) version 16. Results: Nomogram of the thecal sac diameters, lateral recess depth/angle, and neural foramen dimensions were prepared for lumbar vertebra in a sample population. The mean lumbar anterior-posterior diameter and Transverse diameter of thecal sac in the study population were 11.38±1.27mm and 16.75±2.4mm respectively with no significant difference was found by gender (p>0.05). Conclusions: Thecal sac diameters, lateral recess depth, and neural foramen anterior-posterior diameters show a gradual decrease in L1-L2 to L5-S1 level. A spinal morphometric nomogram of the Nepalese population is necessary for assessment of the canal and foraminal compromise as well as surgical approach, technique, instrumentation, and implant development.